Freezing coal anti-sticking agent, preparation method and application thereof

CN122959073APending Publication Date: 2026-10-23LANZHOU SKYLINE ENVIRONMENTAL PROTECTION CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611454468.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-18
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0007]即本发明旨在提供一种冻煤防粘剂和制备方法及其应用,以解决普通防冻在高含水率(15%~30%)与极端低温(-10℃~-40℃)耦合条件下因被煤中水稀释而冰点回升、防冻失效,导致卸煤残留率高、需人工清理的技术问题

Benefits of technology

1.本发明的冻煤防粘剂,通过各组分在分子-微观-宏观多尺度层面的耦合协同实现防粘与阻燃一体化功能:分散剂包覆悬浮剂颗粒并于基体油中形成空间位阻,构成悬浮分散协同,赋予体系贮存稳定与施工流畅性;悬浮剂微粒作为刚性骨架嵌入隔离剂包覆层内,形成界面锚固协同,同时增强涂层附着力和高压持效隔离;基体油浸润后的隔离剂疏水排冰抑制冰核生成,悬浮剂吸附游离水并以微凸起间隙切断冰晶桥接路径,二者构成低温断冰协同,从界面能与物理结构双重阻断煤粒冻结;隔离剂致密层隔氧与阻燃剂化学抑燃时序互补,悬浮剂微孔缓释阻燃产物延长防护时效,构成安全阻燃协同。实验表明,采用本发明的防粘剂后,卸煤时煤块可轻易整体脱落,车厢内壁残留煤量少,且该防粘剂成本低廉,对煤炭热值及后续加工无不良影响,适用于铁路煤炭冬季高含水率运输场景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_11
    Figure SMS_11
Patent Text Reader

Abstract

The application discloses a frozen coal anti-sticking agent and a preparation method and application thereof. The frozen coal anti-sticking agent comprises base oil, suspending agent, dispersing agent, release agent and flame retardant. The anti-sticking and flame-retardant integrated functions are realized through the coupling and cooperation of components in the molecular-microscopic-macroscopic multi-scale level. The suspending agent particles are embedded in the release agent coating layer as a rigid skeleton to form interface anchoring cooperation, and meanwhile, the adhesion of the coating and the high-pressure holding effect of the release are enhanced. The release agent after being infiltrated by the base oil inhibits ice nucleation by hydrophobic ice rejection. The suspending agent absorbs free water and cuts off the ice crystal bridging path through the micro-protrusion gap, and the two constitute low-temperature ice breaking cooperation. The oxygen blocking of the release agent dense layer and the chemical flame-retardant of the flame retardant are complementary in time sequence, the micro-porous slow-release of the suspending agent prolongs the protection time efficiency of the flame retardant product, and safety flame-retardant cooperation is formed. After the anti-sticking agent is used, the coal blocks can be easily and integrally removed during coal unloading, the spraying amount is small, and the anti-sticking agent is suitable for the winter high-water-content transportation scene of railway coal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of antifreeze composite coating technology, specifically relating to an anti-sticking agent for frozen coal, its preparation method, and its application. Background Technology

[0002] Coal, as a crucial basic energy source in my country, is primarily transported long distances by rail. During the mining, washing, and storage processes, coal often carries a high moisture content, especially after water washing, where the moisture content can typically reach 10%–20%, and in some cases even exceed 30%. Coal with a moisture content exceeding 15% is considered high-moisture coal, where surface water and capillary water undergo phase change and freeze under low-temperature conditions. Under conditions of high moisture content (≥15%) and extreme low temperatures (≤-10℃), strong ice bridges easily form between coal particles and between the coal and the inner walls of the wagon, leading to severe freezing and adhesion. After freezing and adhesion between coal particles and between the coal and the wagon walls, a large amount of coal remains on the wagon walls, in corners, and at weld seams during unloading, requiring secondary manual cleaning. This not only reduces unloading efficiency and affects wagon turnover but also increases transportation costs and operational safety risks.

[0003] Currently, the industry mainly employs the following technical solutions to address the aforementioned problems. Physical methods include preheating the inner walls of the coal car, installing vibration devices, and laying lining plates. However, these methods suffer from high equipment investment, high energy consumption, and frequent lining plate replacements, and cannot fundamentally reduce the bonding strength of the frozen interface. Chemical antifreeze methods primarily involve spraying calcium chloride or ethylene glycol-based antifreeze agents onto the coal surface, utilizing the principle of freezing point depression to prevent freezing. However, the effectiveness of these antifreeze agents decreases sharply under high moisture content conditions. When the moisture content exceeds 15%, the antifreeze agent is diluted by a large amount of free water in the coal, causing the freezing point to rise from -52℃ to only -10℃ to -15℃, and completely losing its antifreeze ability below -40℃. In addition, some patents disclose antifreeze release agents based on mineral oils or bio-oils, which achieve antifreeze by forming a water-repellent barrier layer on the surface of the carriage; or coatings using components such as fluorinated resins and polytetrafluoroethylene powder, which utilize their low surface energy properties to reduce the adhesion between coal and the carriage surface; or composite coating structures using epoxy resin primers and fluorinated resin topcoats, which achieve anti-sticking through the low surface energy properties of the topcoat. However, the above technical solutions all belong to the linear design concept of single components or simple physical mixing. Oil-based release agents rely solely on their hydrophobicity to form a physical barrier layer, and fluorocarbon coatings rely solely on their low surface energy properties to achieve anti-sticking. There is a lack of deep synergy and coupling between the components, and it is impossible to simultaneously solve the four interrelated sub-problems of water film displacement, interface anchoring, low-temperature ice breaking, and safe flame retardancy.

[0004] The essence of the failure of the aforementioned existing technologies lies in the fact that frozen coal adhesion is not caused by a single factor, but rather involves a strong coupling of multiple factors, including the continuity of the water film on the coal particle surface (interfacial chemistry), ice crystal nucleation and bridging (phase change thermodynamics), the structural integrity of the isolation layer under high load pressure (micromechanics), and the fire safety of coal mine operations (combustion safety). Single functional components or simple physical mixing schemes are insufficient to simultaneously achieve anti-adhesion effects and safety under coupled operating conditions of high moisture content (15%–30%) and extreme low temperatures (-10℃–-40℃).

[0005] Therefore, how to break away from the traditional linear design thinking of single functional components and construct an anti-sticking agent system with strong adhesion, stable coating, and low freeze-thaw rate and high flame retardant safety at high moisture content (≥15%) and extreme low temperature (≤-10℃) has become a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0006] The essence of the problems in existing technologies lies in four interdependent sub-problems: water film displacement, interfacial anchoring, ice bridge blocking, and flame retardancy, which are difficult to solve simultaneously through a single functional component or simple physical mixing. Based on this, the present invention provides a frozen coal anti-sticking agent composed of a base oil, a suspending agent, a dispersant, a separating agent, and a flame retardant. Unlike the simple combination of components in existing technologies, this invention, through the progressive coupling and synergy of the above five components at the molecular, microscopic, macroscopic, and application scales, enables the same anti-sticking agent system to simultaneously solve the four interdependent sub-problems of water film displacement, interfacial anchoring, ice bridge blocking, and flame retardancy.

[0007] The present invention aims to provide a frozen coal anti-sticking agent and its preparation method and application, in order to solve the technical problem that ordinary antifreeze agents, under the coupled conditions of high moisture content (15% to 30%) and extreme low temperature (-10℃ to -40℃), are diluted by water in the coal and their freezing point rises, resulting in antifreeze failure, high coal unloading residue rate and the need for manual cleaning.

[0008] Specifically, the anti-sticking agent for frozen coal of the present invention comprises the following components in parts by weight: Base oil, 100 parts; Suspension agent, 5-20 parts; Dispersant, 0.5–10 parts; Separating agent, 5-25 parts; Flame retardant, 0.5 to 10 parts.

[0009] In the five-component system of the anti-sticking agent for frozen coal, the base oil serves as both a matrix and a carrier, acting as the core medium connecting the various solid components and running through the four-fold synergistic chain. As the matrix, the base oil constitutes the continuous phase of the entire anti-sticking agent system: on the one hand, it provides a physical platform for the steric hindrance of the non-polar segments of the dispersant to extend, enabling the suspending agent to achieve uniform single-particle-level dispersion in the oil phase; on the other hand, it acts as a suspension medium for the release agent and flame retardant, ensuring that each solid component remains uniformly distributed in the system and guaranteeing the uniformity of the component distribution ratio during spraying.

[0010] Furthermore, as a carrier, the base oil undertakes the functions of transporting solid components and interfacial transfer: due to its low viscosity and excellent wettability on coal particle surfaces, it carries suspending agents, release agents, and flame retardant particles to penetrate into the micro-cracks and contact points on the coal particle surface, providing a medium channel for mechanical anchoring and release agent spreading; its low interfacial tension (γ... LV =25~35mN / m) provides thermodynamic driving force for the spontaneous spreading of the anti-sticking agent on the surface of coal particles, and works synergistically with the interfacial energy reduction effect of the dispersant to achieve water film displacement; during the spraying process, the base oil acts as a flow carrier to deliver each solid component to the coal-steel interface simultaneously, ensuring that the four components reach the action site at the same time in space.

[0011] Furthermore, the suspending agent has a particle size of 200 mesh to 5000 mesh, and includes values ​​at both ends; the suspending agent is selected from one or more of attapulgite, zeolite powder, kaolin, talc powder and calcium carbonate.

[0012] Suspension agents (represented by attapulgite and kaolin) contain a large number of structural hydroxyl groups (-OH) in their crystal structure. Attapulgite is a layered chain silicate mineral, and its edges of silicon-oxygen tetrahedral and octahedral plates, as well as crystal defects, expose abundant silanol groups (≡Si-OH) and aluminumol groups (≡Al-OH). The density of these hydroxyl groups on the crystal surface is approximately 4–8 OH / nm², which is the main source of the surface chemical activity of suspension agents. At room temperature, these hydroxyl groups associate with each other and with water molecules through hydrogen bonds. The bond energy of hydrogen bonds is approximately 20–40 kJ / mol, which is sufficient to keep the hydroxyl groups in a relatively stable associated state. However, it is precisely this association that causes the suspension rod crystals to aggregate in their natural state.

[0013] The suspending agents (attapulgite and kaolin) are inorganic silicate minerals with a Mohs hardness of 2–6 (attapulgite approximately 2–3, kaolin approximately 2–2.5), an elastic modulus of approximately 10–50 GPa, and a compressive strength of approximately 100–300 MPa. In contrast, the continuous phase of the release agent (a composite of fly ash / biomass ash / plant fiber / waste plastic) has a compressive yield strength of approximately 10–30 MPa and an elastic modulus of approximately 0.5–5 GPa. The stiffness (resistance to deformation) of the suspending agent particles is approximately 10–100 times that of the continuous phase of the release agent.

[0014] Furthermore, the release agent is selected from one or more of fly ash, biomass ash, plant fiber, waste plastics, and bentonite, with a particle size of 1000 mesh to 5000 mesh, including values ​​at both ends. The suspending agent particles are embedded in the release agent coating layer as a rigid skeleton, and the two constitute an interface anchoring synergistic system. The mechanical anchoring effect of the suspending agent particles enhances the adhesion of the anti-sticking coating, while its rigid spacing prevents the release agent coating layer from cracking and failing under high pressure stacking. After being impregnated with base oil, the release agent forms a hydrophobic barrier on the surface of coal particles to inhibit ice crystal nucleation. The suspending agent adsorbs free water in the capillaries of coal particles and cuts off the ice crystal bridging path with micro-protrusion gaps. The two constitute a low-temperature ice-breaking synergistic system, blocking the freezing between coal particles from both interfacial energy and physical structure dimensions.

[0015] Furthermore, the flame retardant is selected from one or more of magnesium oxide, petroleum coke powder, aluminum hydroxide and phosphonate, with a particle size of 500 mesh to 5000 mesh, and includes values ​​at both ends; the dense layer of the release agent complements the oxygen barrier and the chemical flame retardant in a complementary sequence, and the microporous structure of the suspending agent acts as a slow-release carrier for the decomposition products of the flame retardant to prolong the flame retardant effect. The three constitute a safe flame retardant synergistic system.

[0016] Furthermore, the base oil includes, but is not limited to, waste engine oil. The dispersant coats the surface of the suspending agent particles and forms a steric hindrance layer in the base oil. The three constitute a suspension-dispersion synergistic system, enabling the anti-sticking agent to have both storage and sedimentation stability and smooth spraying application. The dispersant is selected from one or more of Span 80, Tween 80, sodium dodecyl sulfate, sodium lignosulfonate, and polyacrylamide.

[0017] As amphiphilic compounds, dispersants have polar anchoring groups at one end of their molecular chains chemically bonded to active sites (including Al) on the surface of suspension particles via hydrogen bonds and / or ionic bonds. 3+ Si 4+ The nonpolar hydrophobic segments at the other end of the molecular chain of the metal ions and structural hydroxyl groups extend into the continuous phase of the base oil, forming a steric hindrance layer around the suspending agent particles, inhibiting the aggregation behavior between particles, and making the suspending agent particles uniformly dispersed in the base oil at the single particle level.

[0018] The nonpolar hydrophobic segments of the dispersant are able to extend into the continuous phase of the matrix oil and form a steric hindrance layer around the suspending agent particles, driven by the following forces.

[0019] Dispersants (such as Span 80) are typical amphiphilic compounds whose molecular structure consists of a polar head group (sorbitol ester group) and a nonpolar tail chain (C). 17 H 35It consists of two parts: an unsaturated fatty acid chain and a polar head group. The polar head group acts as an active site on the surface of the suspending agent particles (Al). 3+ Si 4+ The hydroxyl groups (and structural hydroxyl groups) have a strong affinity, forming a chemical anchor through hydrogen bonds and / or ionic bonds; while the nonpolar tail chains bind to the base oil (waste engine oil, whose main component is C). 15 ~C 30 The hydrocarbon mixture has good compatibility and tends to move away from the polar surface and into the non-polar oil phase. This molecular structure of "one end is hydrophilic and the other end is oleophilic" determines that after the dispersant is anchored on the surface of the suspending agent, its non-polar chain segments will spontaneously extend into the continuous phase of the base oil.

[0020] At the molecular scale, interfacial bonding occurs when the polar head groups of dispersant molecules chemically bond with the surface of suspending agent particles via hydrogen / ionic bonds at the nanoscale. This anchors the dispersant molecules firmly to the suspending agent surface, laying the molecular foundation for the subsequent establishment of a steric hindrance layer, reduction of interfacial energy, and water film displacement. This significantly reduces the interfacial free energy of the suspending agent particles from 50–70 mN / m to 20–30 mN / m, allowing the anti-sticking agent to spontaneously spread on the coal particle surface. This replaces the original continuous water film on the surface of high-moisture coal particles with a continuous oil film, thus eliminating the aqueous medium conditions available for ice crystal nucleation and bridging growth on the coal particle surface under low-temperature conditions.

[0021] The present invention also provides a method for preparing the frozen coal anti-sticking agent as described above, comprising the following steps: Step S1: Weigh the base oil according to the ratio and add it to a reactor equipped with a heating device, thermometer, and anchor stirrer for vacuum dehydration until the water content of the system is <0.3%. Observe the sight glass of the reactor during the dehydration process until no obvious water mist escapes. After the water content is qualified, take a sample to measure and then cool it down to 80-110℃ and keep it at a constant temperature for later use.

[0022] Step S2: Take the suspending agent, separating agent and flame retardant according to the proportion and place them in a forced-air drying oven. Dry them at 80-120℃ until the moisture content is <0.5%. Transfer the dried solid powder into a sealed container while it is still hot and cool it to room temperature for later use to prevent moisture absorption and re-moistening.

[0023] Step S3: At a constant temperature of 80-110°C, start a high-speed dispersing mixer and slowly add the suspending agent to the base oil at a feeding rate of 5-10 g / min. After the addition is complete, continue stirring for 10-20 minutes to ensure that the suspending agent particles are fully wetted by the base oil.

[0024] Step S4: In the mixing system of step S3, the dispersant is added to the reactor at a feeding rate of 2-5 g / min while the stirring speed remains unchanged. The system state is observed during stirring until the system is a uniform, viscous fluid without obvious particle clumps and without particle sedimentation.

[0025] Step S5: Dry mix the release agent and flame retardant evenly in a premix tank, reduce the stirring speed, and add them to the reaction vessel of step S4 at a feeding rate of 10-20 g / min. Maintain the temperature at 80-110℃ and continue stirring for 30-90 minutes.

[0026] The suspending agent must first be added to the base oil and dispersed under high shear, followed by the addition of a dispersant to initiate an interfacial bonding reaction. Only after the suspending agent rods have fully dissociated and a steric hindrance layer has been established can the release agent and flame retardant be added. This irreversible sequence ensures that the dispersant preferentially and fully bonds to the surface of the suspending agent, avoiding competitive adsorption by the release agent or flame retardant, which is a prerequisite for establishing molecular-scale synergy.

[0027] Step S6: Stop heating and adjust the stirring speed to 100-300 r / min, allowing the system to cool naturally to room temperature while stirring to obtain the frozen coal anti-sticking agent. The purpose of controlling the low-speed stirring in this step is to prevent the re-aggregation of the suspending agent rod crystals during the cooling process, and to prevent particle sedimentation due to static setting.

[0028] The entire preparation process is maintained at 80–120°C. This ensures thorough dehydration of the system, preventing water molecules from occupying the active sites of the hydroxyl groups on the surface of the suspending agent. It also provides thermodynamic activation energy for establishing a hydrogen bond network between the structural hydroxyl groups of the suspending agent and the oxygen-containing functional groups of the isolating agent. Below 80°C, the binding energy barrier of the hydrogen bond network cannot be overcome, and atomic-scale interfacial bonding does not form. Above 120°C, the microporous structure of the suspending agent may be damaged, leading to thermal degradation of the dispersant.

[0029] The suspending agent microparticles achieve a triple synergistic effect at the microscopic level: First, at preparation temperatures of 80–120℃, the silanol groups on the surface of the microparticles overcome the hydrogen bond association energy barrier with the carboxyl and siloxy groups of the release agent, constructing a three-dimensional hydrogen bond network across two phases, providing an atomic-level interfacial bonding force of 20–40 kJ / mol. After cooling, the microparticles and the release agent coating layer achieve a tight bond without delamination. At the same time, the micro-nano particles of the release agent penetrate into the micropores on the coal surface to form a micro-rivet anchoring structure, improving the adhesion of the coating. Second, the rigid microparticles dispersed in the release agent coating layer act as a microscopic support skeleton, bearing the vertical load under the high pressure of coal loading, opening up the microscopic gaps in the coating layer, inhibiting the pressure collapse and cracking of the release agent coating layer, and continuously maintaining the integrity of the isolation barrier. Third, the interfacial hydrogen bonds can eliminate the microscopic agglomeration of the suspending agent powder itself, achieving a monodisperse distribution of microparticles, ensuring the uniform and stable microscopic properties of the coal surface coating, and solving the microscopic defects of traditional coatings such as poor adhesion, easy damage under high pressure, and uneven antifreeze performance.

[0030] Furthermore, during vacuum dehydration in step S1, stirring is started, with the speed controlled at 200-400 r / min, the temperature raised to 80-120℃, and the mixture is stirred at a constant temperature for 10-120 minutes under a vacuum of -0.08 to -0.095 MPa.

[0031] Furthermore, in step S3, the speed of the high-speed dispersing stirrer is controlled at 800–1500 r / min; in step S4, the stirring speed is maintained at 800–1500 r / min, the temperature at 80–110℃, and the stirring time is 30–90 minutes. The high shear rate of 800–1500 r / min during the dispersion stage provides sufficient mechanical energy to dissociate the hydrogen bonds between the suspending agent rod crystals, ensuring that the active groups of the dispersant fully contact the active sites on the particle surface.

[0032] Furthermore, in step S5, the stirring speed is adjusted to 500–800 r / min. The technical purpose of reducing the stirring speed to 500–800 r / min in this step is to ensure that the release agent and flame retardant are uniformly dispersed in the system, while avoiding excessive shear force that could damage the already formed three-dimensional thixotropic network structure of the suspension. The system state is observed during mixing until the system becomes a uniform, consistent paste-like fluid without obvious particle stratification or agglomeration.

[0033] After being thermally activated at 80–120 °C during the preparation process, the structural hydroxyl groups on the surface of the suspending agent and the oxygen-containing functional groups on the surface of the separating agent form inter-component atomic-level interfacial bonds through a hydrogen bond network. This allows the suspending agent particles to be firmly embedded in the continuous phase of the separating agent as a rigid skeleton, forming a composite separating layer structure with the rigid suspending agent particles as the reinforcing skeleton and the flexible matrix of the separating agent as the continuous phase.

[0034] The suspending agent is a high-energy surface (50-70 mN / m), and the isolating agent is a relatively low-energy continuous phase (25-40 mN / m). The system tends to replace the high-energy solid-gas interface with the low-energy solid-solid interface, driving the isolating agent molecular chains to spontaneously encapsulate the suspending agent particles, achieving thermodynamically stable wetting and encapsulation.

[0035] At a preparation temperature of 80–120 °C, the hydroxyl groups (-OH) on the surface of the suspending agent and the oxygen-containing functional groups (Si-O-Si, -COOH, etc.) on the surface of the isolating agent overcome the hydrogen bond association energy barrier to form a cross-component hydrogen bond network, providing atomic-level bonding force (bonding energy 20–40 kJ / mol) to the interface, so that the particles remain firmly bonded to the matrix after cooling.

[0036] ; ; The particle size of the suspending agent (2.6–74 μm) is much larger than the theoretical equivalent thickness of the release agent (1.69–2.44 μm), and the particles penetrate the release layer to form a "pinning" structure. At the same time, the molecular chain segments of the release agent are in a highly mobile state at 80–120 °C, and can undergo local rearrangement to adapt to the surface topology of the particles, thus achieving tight encapsulation.

[0037] Before the release agent is added, the dispersant has already dissociated the suspending rod crystal bundles into a single particle-level uniform dispersion state, ensuring that the suspending particles are distributed in the system with a uniform spatial density when the release agent is added, so that the composite release layer has a macroscopically uniform rigid-flexible distribution.

[0038] The composite isolation layer further leverages the dual-mode synergistic anti-icing mechanism of hydrophobic de-icing and physical icing inhibition: Hydrophobic de-icing: After the release agent is impregnated with base oil and coated on the surface of coal particles, the surface energy of the coal particles is reduced from 60-70 mN / m (hydrophilic) in raw coal to ≤25 mN / m (hydrophobic). According to the classical heterogeneous nucleation theory, the free energy barrier for ice crystal nucleation ΔG is proportional to the square of the free energy γ at the solid-liquid interface. The decrease in interfacial energy increases the critical nucleation radius of ice crystals and causes the nucleation rate to decrease exponentially, thereby inhibiting heterogeneous nucleation of ice crystals on the surface of coal particles at the thermodynamic level of interfacial energy.

[0039] Physical ice inhibition: The suspending agent microparticles physically adsorb and lock the free water in the capillary channels of coal particles through their microporous structure (pore size 2-50nm), preventing the free water from migrating to the coal particle contact point to participate in ice crystal growth during the cooling process; at the same time, the suspending agent microparticles act as rigid spacers to create micron-level gaps (≥2μm), preventing ice crystals from crossing these gaps to complete the overlap between adjacent coal particles during the growth process, thus physically cutting off the continuous growth path of ice crystals.

[0040] In this invention, the theoretical equivalent thickness of the composite isolation layer is 1.69 to 2.44 μm, and the theoretical number of composite covering layers of the suspending agent and the isolation agent is between 0.43 and 0.71 layers (both much less than 1 layer). This indicates that the composite isolation layer does not cover the surface of the coal particles in the form of a continuous and complete film, but is distributed between the coal particles in the form of a discrete rigid skeleton and a local covering morphology.

[0041] This structural feature determines that the anti-sticking mechanism of the present invention is not achieved through complete encapsulation, but through a co-continuous composite network formed by the suspending agent and the isolating agent under atomic-scale hydrogen bonding, which creates a micron-level physical gap (≥2μm) between the coal particles and the carriage wall, preventing ice crystals from crossing this gap to complete the bridging between adjacent coal particles during the growth process, thereby cutting off the formation path of ice bridges at the physical topology level.

[0042] Sequential gradient protection of release agents, flame retardants, and suspension inhibitors: The release agent, flame retardant, and suspending agent work sequentially at different stages of temperature rise, forming a three-stage sequential flame retardant protection: In the first stage (room temperature to 200℃), the dense layer of plant fiber / waste plastic components in the release agent forms a physical oxygen barrier; in the second stage (200℃ to 400℃), the flame retardant aluminum hydroxide decomposes and releases water of crystallization, absorbing heat and cooling down, while magnesium oxide promotes char formation; in the third stage (≥400℃), the microporous framework of the suspending agent performs confined adsorption and slow release of gaseous active species generated by the decomposition of the flame retardant, extending the free radical capture lifetime from ≤5s in the traditional system to ≥30s.

[0043] The present invention also provides an application of the frozen coal anti-sticking agent as described above. The application method is as follows: first, the frozen coal anti-sticking agent is evenly sprayed on the inner wall and bottom of the car body, with a spraying amount of 20-80 grams per square meter; then, the coal is loaded into the car body within 48 hours after spraying.

[0044] Compared with the prior art, the advantages of the present invention are as follows: 1. The anti-sticking agent for frozen coal of the present invention achieves integrated anti-sticking and flame-retardant functions through the coupling and synergy of each component at multiple scales from molecular to micro to macro: the dispersant coats the suspending agent particles and forms steric hindrance in the base oil, constituting a suspension-dispersion synergy, giving the system storage stability and smooth construction; the suspending agent particles are embedded in the release agent coating layer as a rigid skeleton, forming an interface anchoring synergy, while enhancing the coating adhesion and high-pressure sustained isolation; the release agent after being wetted by the base oil is hydrophobic and ice-removing, inhibiting ice nucleus formation, and the suspending agent adsorbs free water and cuts off the ice crystal bridging path with micro-protrusion gaps, the two constituting a low-temperature ice-breaking synergy, blocking the freezing of coal particles from both interface energy and physical structure; the oxygen-barrier dense layer of the release agent and the chemical flame-suppressing sequence of the flame retardant complement each other, and the microporous slow-release flame-retardant products of the suspending agent prolong the protective effect, constituting a safe flame-retardant synergy. Experiments show that after using the anti-sticking agent of the present invention, coal blocks can be easily detached as a whole during unloading, with little coal residue on the inner wall of the car. Moreover, the anti-sticking agent is inexpensive and has no adverse effects on the calorific value of coal or subsequent processing, making it suitable for railway coal transportation scenarios with high moisture content in winter.

[0045] 2. This invention establishes a four-fold progressive coupling and synergistic system through interfacial anchoring at the molecular scale between the dispersant, suspending agent, and base oil; steric hindrance; hydrogen bond network bonding at the atomic scale between the dispersant and suspending agent; a dual-mode synergistic effect of hydrophobic anti-icing and physical anti-icing at the microscale between the release agent, which is impregnated with the base oil, and the suspending agent; and a time-gradient flame-retardant synergistic effect between the release agent, flame retardant, and suspending agent at the application scale. This synergistic system makes the anti-sticking agent of this invention significantly superior to the control system composed of any single component or simple physical mixture in terms of storage stability, interfacial spreadability, coating adhesion, low-temperature antifreeze adhesion performance, and flame-retardant safety. Detailed Implementation

[0046] The present invention will be further described below with reference to the embodiments; in the present invention, unless otherwise specified, all raw materials used in the preparation are commercially available products well known to those skilled in the art.

[0047] Example 1 This embodiment provides a method for preparing a frozen coal anti-sticking agent, which includes the following components in parts by weight: 100 parts waste engine oil, 10 parts attapulgite clay of 1250 mesh, 3 parts Span 80, 15 parts fly ash of 2000 mesh, and 3 parts magnesium oxide of 800 mesh.

[0048] The preparation method of the anti-sticking agent for frozen coal in this embodiment includes the following steps: Step 1: Weigh the waste engine oil according to the ratio and add it to the reactor equipped with a heating device, thermometer and anchor stirrer. Start stirring, control the speed at 300 r / min, raise the temperature to 90℃, and dehydrate under vacuum conditions of -0.09MPa for 60 minutes.

[0049] Step 2: Weigh out the attapulgite, fly ash, and magnesium oxide according to the proportions and place them separately in a forced-air drying oven. Dry them at 90℃ until the moisture content is <0.5%. Transfer the dried solid powder to a sealed container while it is still hot and let it cool to room temperature before use to prevent moisture absorption and re-moistening.

[0050] Step 3: At a constant temperature of 90℃, start a high-speed dispersing mixer and control the speed at 1300r / min. Slowly add attapulgite clay to the base oil at a feeding rate of 5g / min. After the feeding is completed, continue stirring for 20 minutes to ensure that the attapulgite clay particles are fully wetted by the waste oil.

[0051] Step 4: In the mixing system of Step 3, Span 80 is slowly added to the reactor at a feeding rate of 3 g / min, while maintaining a stirring speed of 1400 r / min and a temperature of 90℃ for 60 minutes.

[0052] Step 5: Adjust the stirring speed to 600 r / min, pre-mix the fly ash and magnesium oxide evenly in the premixing tank, and then slowly add them to the reaction vessel in Step 4 at a feeding rate of 150 g / min. Maintain the temperature at 90℃ and continue stirring for 60 minutes. In this step, reduce the stirring speed to 600 r / min.

[0053] Step 6: Stop heating, adjust the stirring speed to 200 r / min, and allow the system to cool naturally to room temperature while stirring to obtain the frozen coal anti-sticking agent.

[0054] Example 2 This embodiment also provides a method for preparing a frozen coal anti-sticking agent, specifically referring to Embodiment 1. The difference between this embodiment and Embodiment 1 is that: in this embodiment, the suspending agent is composed of 5 parts attapulgite clay and 5 parts zeolite powder, the separating agent is composed of 10 parts biomass ash and 5 parts plant fiber, and the flame retardant is aluminum hydroxide.

[0055] Example 3 This embodiment also provides a method for preparing a frozen coal anti-sticking agent, specifically referring to Embodiment 1. The difference between this embodiment and Embodiment 1 is that the suspending agent in this embodiment is composed of 6 parts kaolin and 4 parts talc, the separating agent is bentonite, and the flame retardant is petroleum coke powder.

[0056] Example 4 This embodiment also provides a method for preparing a frozen coal anti-sticking agent, specifically referring to Embodiment 1. The difference between this embodiment and Embodiment 1 is that: in this embodiment, the suspending agent is composed of 12 parts of attapulgite and 8 parts of calcium carbonate, Span 80 is 6 parts, the release agent is composed of 10 parts of waste plastic and 5 parts of bentonite, and the flame retardant is zero ester.

[0057] Example 5 This embodiment also provides a method for preparing a frozen coal anti-sticking agent, specifically referring to Embodiment 1. The difference between this embodiment and Embodiment 1 is that in this embodiment, the dispersant attapulgite is 200 mesh, the release agent fly ash is 1000 mesh, and the flame retardant magnesium oxide is 500 mesh.

[0058] Example 6 This embodiment also provides a method for preparing a frozen coal anti-sticking agent, specifically referring to Embodiment 1. The difference between this embodiment and Embodiment 1 is that the dispersant attapulgite is 5000 mesh, the release agent fly ash is 5000 mesh, and the flame retardant magnesium oxide is 5000 mesh.

[0059] Comparative Example 1 The anti-sticking agent for frozen coal in this comparative example is a commercially available calcium chloride-based antifreeze for railway transportation of coal. Referring to the industry standard TB / T3208-2023 "Antifreeze Agents for Railway Bulk Particle Cargo Transportation" and based on publicly available literature, its typical formula is: 33% industrial calcium chloride, 0.5% borax, 0.15% sodium nitrite, 0.3% triethanolamine, and the remainder is water.

[0060] Comparative Example 2 This comparative example also provides a method for preparing a frozen coal anti-sticking agent, specifically referring to Example 1. The difference between this comparative example and Example 1 is that this comparative example does not contain a separating agent.

[0061] Comparative Example 3 This comparative example also provides a method for preparing a frozen coal anti-sticking agent, specifically referring to Example 1. The difference between this comparative example and Example 1 is that this comparative example does not contain a suspending agent.

[0062] Comparative Example 4 This comparative example also provides a method for preparing a frozen coal anti-sticking agent, specifically referring to Example 1. The difference between this comparative example and Example 1 is that this comparative example does not contain a dispersant.

[0063] Comparative Example 5 This comparative example also provides a method for preparing a frozen coal anti-sticking agent, specifically referring to Example 1. The difference between this comparative example and Example 1 is that this comparative example does not contain a flame retardant.

[0064] Comparative Example 6 This comparative example also provides a method for preparing a frozen coal anti-sticking agent. Specifically, refer to Example 1. The difference between this comparative example and Example 1 is that in step 1 of this comparative example, the waste engine oil is heated to 40°C and vacuum dehydrated for 60 minutes under a vacuum of -0.09MPa while maintaining a constant temperature.

[0065] This means that the preparation temperature in this comparative example was too low, and the waste oil was not fully dehydrated.

[0066] Comparative Example 7 This comparative example also provides a method for preparing a frozen coal anti-sticking agent, specifically referring to Example 1. The difference between this comparative example and Example 1 is that in step 1 of this comparative example, the suspending agent attapulgite powder is 6000 mesh, the release agent fly ash is 2000 mesh, and the flame retardant magnesium oxide is 800 mesh.

[0067] Comparative Example 8 This comparative example also provides a method for preparing a frozen coal anti-sticking agent, specifically referring to Example 1. The difference between this comparative example and Example 1 is that the fly ash in this comparative example is 800 mesh. That is, the particle size of the release agent in this comparative example is too coarse.

[0068] Comparative Example 9 This comparative example also provides a method for preparing a frozen coal anti-sticking agent. Specifically, refer to Example 1. The difference between this comparative example and Example 1 is that the flame retardant magnesium oxide in this comparative example is 6000 mesh, that is, the flame retardant particle size in this example is too fine.

[0069] Application examples The anti-sticking agents for frozen coal of Examples 1-6 and Comparative Examples 1-9 were uniformly sprayed onto the inner wall and bottom of the car body at a spraying amount of 80 grams per square meter. Within 48 hours after spraying, coal with moisture contents of 15% and 30% respectively was loaded into the car body and placed in a -40°C low-temperature environment for 72 hours to freeze.

[0070] The particle size, low-temperature stability, settling rate (0℃, 72h), coating adhesion, equilibrium spread coefficient, self-extinguishing time after flame removal, spraying amount, and freeze-thaw rate (15% / -40℃, 30% / -40℃) of the anti-sticking agents in the examples and comparative examples were measured. Among them: The method for determining particle size is as follows: Take powder samples from each example or comparative example, and use a laser particle size analyzer to determine their particle size distribution according to GB / T19077-2024. Read the D50 median diameter and convert it into mesh size. The arithmetic mean of three parallel determinations is used as the final result.

[0071] The method for testing low-temperature stability is as follows: Take the anti-sticking agent samples from each example or comparative example and store them at -20℃ for 168 hours. After removal, visually inspect them. If the sample has no precipitates and appears as a homogeneous fluid, it indicates that the anti-sticking agent sample has low-temperature stability.

[0072] The sedimentation rate was tested using the graduated cylinder sedimentation method: the prepared anti-sticking agent sample was poured into a 100 mL stoppered graduated cylinder and sealed at 0℃ for 72 hours. The volume (mL) of the supernatant was observed and measured visually. Sedimentation rate (%) = (volume of supernatant / total volume) × 100%.

[0073] The method for the spreadability test is as follows: Coal particles with a moisture content of 25% are spread evenly and compacted on the surface of a glass slide. An anti-sticking agent is dropped onto the surface of the coal sample, and the apparent static contact angle θ is measured using a contact angle meter. At the same time, the liquid-gas surface tension of the anti-sticking agent is measured. According to Young's equation: Calculate the apparent spreading factor of the anti-sticking agent on the coal sample surface: ; in, The equilibrium spreading factor is expressed in mN / m, which is numerically equivalent to mJ / m. 2 ; The surface tension between liquid and gas. When When the value is closer to 0, it indicates a stronger tendency for the anti-sticking agent to spread on the coal sample surface. Due to the rough, porous, and heterogeneous characteristics of wet coal surfaces, the contact angle and spreading coefficient obtained in this study are mainly used for relative comparisons of the spreading performance of different anti-sticking agents. In this invention, the adsorption of the dispersant at the coal-anti-sticking agent interface may help reduce the apparent solid-liquid interfacial free energy, while the low surface tension matrix oil makes the anti-sticking agent system... Maintaining at approximately 25 mN / m, the two work synergistically to promote the spreading of the anti-sticking agent on the wet coal surface and the coverage of the oil film.

[0074] The self-extinguishing time after flame removal is determined using a flame burning test: The anti-sticking agent is uniformly coated onto the surface of a standard-sized substrate to form a coating; the substrate is selected from asbestos board or stainless steel plate. A standard flame source (Bunsen lamp or alcohol torch) is used to ignite the coating surface for 5-10 seconds, then the flame source is removed, and the time required for the flame on the coating surface to completely extinguish is immediately recorded using a stopwatch. This time is recorded as the afterflame time. The shorter the afterflame time, the better the flame retardant performance of the anti-sticking agent.

[0075] The test method for freeze-sticking rate is as follows: Using a tipper unloading device, a steel plate coated with anti-sticking agent, along with a frozen coal sample, is placed on a tilting platform. Coal is unloaded at a tilting angle of 135° and a tilting speed of 10 mm / s. The amount of residual coal is recorded, and the freeze-sticking rate is calculated based on the amount of residual coal. Calculation formula: Freeze-sticking rate (%) = (Mass of residual frozen coal at the interface / Initial total coal loading mass) × 100%.

[0076] The results of low-temperature stability, sedimentation rate (0℃, 72h), self-extinguishing time after flame removal, spraying amount, and freeze-thaw rate of the anti-sticking agents in each embodiment and comparative example are shown in Table 1:

[0077] Table 1. Statistical results of particle size, low-temperature stability, sedimentation rate (0℃, 72h), self-extinguishing time after flame removal, spraying amount, and freeze-thaw rate (15% / -40℃, 30% / -40℃) of the anti-sticking agent: This invention comprehensively verifies the synergistic effect of each component through a systematic comparative experiment using Examples 1-6 and Comparative Examples 1-9. Experimental data show that the five components described in this invention do not exhibit a simple superposition of known properties, but rather produce unexpected technical effects through multi-scale progressive synergy.

[0078] Comparative Example 4 (without dispersant) had a spreading coefficient S = -8.8, indicating that the anti-sticking agent could not spread on the surface of coal particles, and the continuous water film on the surface of high-moisture coal particles could not be displaced, resulting in a settling rate ≥28% and a freeze-thaw rate ≤19%. In contrast, Example 1 (with dispersant) had a spreading coefficient S = -1.2, indicating that the anti-sticking agent could spontaneously spread and displace the water film into an oil film, resulting in a settling rate ≤3.2%, good low-temperature stability, and a freeze-thaw rate of only 7.8%. The only difference between the two formulations was the presence or absence of a dispersant; without a dispersant, the suspending agent agglomerated, the water film was not displaced, and the subsequent synergistic chain broke.

[0079] Comparative Example 6 had the same formulation as Example 1 (100 parts waste engine oil, 10 parts attapulgite, 3 parts Span 80, 15 parts fly ash, and 3 parts magnesium oxide). The only difference was the preparation temperature: Comparative Example 6 was prepared at 40°C, while Example 1 was prepared at 90°C. At 40°C, moisture was not fully removed, and a hydrogen bond network could not be established between the hydroxyl groups on the surface of the suspending agent and the oxygen-containing functional groups of the isolating agent. The composite isolating layer did not form, and the freeze-thaw rate increased from 7.8% to 23%. This comparison demonstrates that interfacial bonding at the atomic scale requires a certain temperature for thermal activation to be triggered; insufficient temperature prevents bonding from forming, and synergy is ineffective.

[0080] Comparative Example 2 (without release agent) had a freeze-sticking rate of 32%, which was higher than that of Example 1, and a self-extinguishing time of >15 seconds, proving that the lack of release agent caused the hydrophobic de-icing mode to be completely ineffective and the first flame retardant sequence was missing.

[0081] Comparative Example 3 (without suspending agent) showed a freeze-thaw rate of 20%, unstable low-temperature stability and stratification, and a self-extinguishing time extended to 4.5 seconds, proving that the lack of suspending agent caused the complete breakdown of interface anchoring synergy, low-temperature ice-breaking synergy and flame-retardant third sequence.

[0082] Comparative Examples 2 and 3 show that the release agent and the suspending agent form a synergistic pair with complementary functions at the microscale: after being wetted by the base oil, the release agent is responsible for hydrophobic ice removal and physical oxygen isolation, while the suspending agent is responsible for rigid separation, mechanical anchoring and microporous slow release. Both are indispensable.

[0083] Comparative Example 5 (without flame retardant) had a self-extinguishing time >15 seconds, which is higher than that of Example 1 (≤2.0 seconds), and a limiting oxygen index <21%, failing to meet coal mine safety requirements; however, its anti-sticking performance was basically the same as that of Example 1 (freeze-sticking rate ≤8.5%). This comparison proves that the flame retardant only participates in the safety flame retardant synergy (second time sequence). Although its absence does not affect the antifreeze and anti-sticking functions, it leads to the product losing its practical safety. This further verifies that the anti-sticking and flame retardant functions of the present invention are synergistically undertaken by different components, and the absence of either one results in incomplete overall performance.

[0084] In Comparative Example 1, conventional antifreeze, under coupled conditions of -40℃ and high water content (15%–30%), completely failed due to dilution by water in the coal, causing its freezing point to rise to -10℃–-15℃, resulting in a freeze-thaw viscosity rate ≥65%. In contrast, Example 1, under the same conditions, exhibited a freeze-thaw viscosity rate of only 7.8%. This comparison demonstrates that the traditional freezing point reduction mechanism completely fails due to the dilution effect under coupled conditions of high water content and extreme low temperatures. In contrast, this invention, through dual-mode synergy, blocks freezing from both interfacial energy and physical topology dimensions, achieving an antifreeze effect that a single mechanism cannot achieve.

[0085] In this invention, if the components only have simple functional superposition without synergistic effects, the theoretical freeze-thaw rate of the complete five-component system should be close to a linear combination of the freeze-thaw rates of the systems lacking individual components. However, the average freeze-thaw rate of Comparative Example 2 (lacking release agent, 32%), Comparative Example 3 (lacking suspending agent, 20%), Comparative Example 4 (lacking dispersant, ≤19%), and Comparative Example 5 (lacking flame retardant, ≤10%) is (32%+20%+19%+10%) / 3≈20.3%, while the actual freeze-thaw rate of the complete system in Example 1 is only 7.8%.

[0086] This superposition effect is direct quantitative evidence of the synergistic effect of the present invention: the actual anti-sticking effect of the complete five-component system is far better than the simple linear superposition of the components, proving that the five components generate significant synergistic gains through multi-scale progressive coupling.

[0087] Finally, it should be noted that the above specific embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.

Claims

1. A frozen coal anti-sticking agent, characterized in that, It contains the following components in parts by weight: Base oil, 100 parts; Suspension agent, 5-20 parts; Dispersant, 0.5–10 parts; Separating agent, 5-25 parts; Flame retardant, 0.5–10 parts; The base oil constitutes the continuous phase of the entire anti-sticking agent system; The suspending agent particles are embedded in the release agent coating layer as a rigid skeleton, and the two constitute an interface anchoring synergistic system. The release agent forms a hydrophobic barrier on the surface of coal particles after being wetted with base oil to inhibit ice crystal nucleation. The suspending agent adsorbs free water in the capillaries of coal particles and cuts off the ice crystal bridging path with micro-protrusion gaps. The dense layer of the release agent provides oxygen isolation, which complements the chemical flame-retardant sequence. Furthermore, the microporous structure of the suspending agent acts as a slow-release carrier for the decomposition products of the flame retardant, extending the flame-retardant effect.

2. The anti-sticking agent for frozen coal according to claim 1, characterized in that, The suspending agent has a particle size of 200 mesh to 5000 mesh, including values ​​at both ends; the suspending agent is selected from one or more of attapulgite, zeolite powder, kaolin, talc powder and calcium carbonate.

3. The anti-sticking agent for frozen coal according to claim 1, characterized in that, The release agent is selected from one or more of fly ash, biomass ash, plant fiber, waste plastic and bentonite, with a particle size of 1000 mesh to 5000 mesh, and includes values ​​at both ends.

4. The anti-sticking agent for frozen coal according to claim 1, characterized in that, The flame retardant is selected from one or more of magnesium oxide, petroleum coke powder, aluminum hydroxide and phosphonate, with a particle size of 500 mesh to 5000 mesh, and includes values ​​at both ends.

5. The anti-sticking agent for frozen coal according to claim 1, characterized in that, The base oil includes waste engine oil, and the dispersant is selected from one or more of Span 80, Tween 80, sodium dodecyl sulfate, sodium lignosulfonate, and polyacrylamide.

6. A method for preparing the anti-sticking agent for frozen coal according to any one of claims 1-5, characterized in that, Includes the following steps: Step S1: Weigh the base oil according to the proportion and add it to a reaction vessel equipped with a heating device, thermometer and anchor stirrer for vacuum dehydration until the water content of the system is <0.3%. Then cool it down to 80-110℃ and keep it at a constant temperature for later use. Step S2: Take the suspending agent, separating agent and flame retardant according to the proportion and place them in a forced-air drying oven. Dry them at 80-120℃ until the moisture content is <0.5%. Transfer the dried solid powder into a sealed container and cool it to room temperature for later use. Step S3: At a constant temperature of 80-110°C, start a high-speed dispersing mixer and add the suspending agent to the base oil at a feeding rate of 5-10 g / min. After the addition is complete, continue stirring for 10-20 minutes. Step S4: In the mixing system of step S3, the dispersant is added to the reactor at a feeding rate of 2-5 g / min while the stirring speed remains constant. Step S5: Dry mix the release agent and flame retardant evenly in a premixing tank, reduce the stirring speed, and add them to the reaction vessel of step S4 at a feeding rate of 10-20 g / min, and continue stirring; Step S6: Stop heating, adjust the stirring speed to 100-300 r / min, and allow the system to cool naturally to room temperature to obtain the frozen coal anti-sticking agent.

7. The method according to claim 6, characterized in that: In step S1, when performing vacuum dehydration, start stirring, control the speed at 200-400 r / min, raise the temperature to 80-120℃, and stir at a constant temperature for 10-120 minutes under a vacuum of -0.08--0.095 MPa.

8. The method according to claim 6, characterized in that: In step S3, the speed of the high-speed dispersing mixer is controlled at 800-1500 r / min; in step S4, the stirring speed is maintained at 800-1500 r / min, the temperature at 80-110℃, and the stirring time is 30-90 minutes.

9. The method according to claim 6, characterized in that: In step S5, the stirring speed is adjusted to 500-800 r / min.

10. The application of the anti-sticking agent for frozen coal as described in any one of claims 1-5 or prepared according to any one of claims 6-9, characterized in that, The application method is as follows: First, spray the anti-sticking agent for frozen coal evenly on the inner wall and bottom of the car body, with a spraying amount of 20-80 grams per square meter; then load the coal into the car body within 48 hours after spraying.